Honesty is predicted by moral values and economic incentives but is unaffected by acute stress - Sooter, Nina M.; Brandon, Rajna Gibson; Ugazio, Giuseppe (Journal of behavioral and experimental finance, 2024)
Being truthful in financial decision-making often implies giving up higher monetary rewards associated with acting dishonestly. Is this trade-off affected by acute stress? We ran an experimental study to answer this question. Using three separate tasks to measure honesty, we examined whether decision-making in this context is influenced by a) the intrinsic value that subjects assign to honesty, b) the size of earnings achievable dishonestly, and c) by being acutely stressed (vs. in a neutral state) when making these decisions. Our main results show that subjects’ stated preference for honesty in general, the magnitude of financial rewards, and their interaction predict honest decision-making. However, their effects are immune to acute stress, which did not significantly alter honest decision-making. This finding is important when one considers that many financial decisions are taken by stressed managers and that there are significant costs associated with implementing ethical policies within corporations.